Pin tract infection caused by Mycobacterium neoaurum in a 14-year-old child: A case report. Issue 8 (August 2021) - Kusano, Taizo; Fukasawa, Chie; Yamamoto, Shota; Shiratori, Erika; Murata, Shota; Takaki, Akiko; Chikamatsu, Kinuyo; Mitarai, Satoshi; Hoshino, Tadashi
Abstract: Although rapidly growing non-tuberculosis mycobacterium can occasionally cause postoperative infections, Mycobacterium neoaurum is a rare pathogen of surgical site infection. We report a case of pin tract infection caused by M. neoaurum in a 14-year-old girl who was admitted for lengthening of her right fourth metatarsal bone. Pain, redness, and exudate were observed 18 days after external fixator insertion. Repeated exudate cultures revealed M . neoaurum, and she was diagnosed with a mycobacterial pin tract infection. She was initially administered intravenous ciprofloxacin and minocycline, and then was switched to oral trimethoprim-sulfamethoxazole and minocycline for a total of 6 months. Despite the pin tract infection, bone lengthening was completed under antibiotic treatment without removal of the pin; no other complications were noted. There are no prior reports of external fixator pin tract infection by M. neoaurum . While such cases may be rare, this case demonstrates that bone distraction may still be successfully completed using appropriate antibiotic therapy without pin removal.